PENGARUH METODE BERCERITA TERHADA PENINGKATANTANGGUNG JAWAB ANAK USIA 5-6 TAHUN DI TK IT CAHAYA BINTANG KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - muharni, lara (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research endeavors to investigate the heightened sense of responsibility among 5-6-year-old children at TK IT Cahaya Bintang, Sungai Kakap District, Kubu Raya Regency. Employing a quantitative experimental approach, the study draws data from group B children aged 5-6, utilizing observation sheets comprising checklists and documentation. Initial findings during the pretest observation indicate a nascent development of responsibility, averaging at 49. Subsequent posttest observations, following increased treatment, reveal a noteworthy progression to an expected level, averaging at 67.4.  Statistical analysis through the T-test results in the rejection of the null hypothesis (Ho), with the acceptance of the alternative hypothesis, as evidenced by tcount ttable (10.531 2.145). This implies a significant impact of the storytelling method on the responsibilities of 5-6-year-old children in IT Kindergarten, Cahaya Bintang District, Kakap River, Kubu Raya Regency. To sum up, the utilization of storytelling in children's activities influences their sense of responsibility, enabling them to comprehend positive and negative traits, characters, and behaviors. It is envisaged that educators can provide suitable stimuli to cultivate responsible attitudes in children, fostering a sense of responsibility for both themselves and others.